Constructing the Stock Exchange. On the Rise and Fall of an Iconic Place of Capitalism - Johannes W. Flume (Rechtsgeschichte - Legal History)
Marketplaces are fascinating locations for studying socio-economic interactions. One of the most prominent of these places were bourses or stock exchanges. Only very recently and almost unnoticed, the hectic physical spaces of these trading venues have been emptied, following the increased use of electronic trading and the end of parquet trading.This brought to a sudden end the 500-year-old institution as we know it: a physical space dedicated to the sole purpose of meeting, exchanging information, and trading. This article seeks to provide a concise history of constructing and reﬁning one of the most iconic places of capitalism. I argue that combining the architectural history of exchange buildings with an analysis of the legal and economic purpose of the institution provides a powerful tool for locating and evaluating the impact of technological advances on commerce in global history.